2021
DOI: 10.1029/2021ja029109
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Electron Pressure to Ring Current and Ground Magnetic Depression Using RAM‐SCB Simulations and Arase Observations During 7–8 November 2017 Magnetic Storm

Abstract: There is increased interest recently in understanding Sun-Earth interactions and space weather events due to the increasing reliability on space-based technological systems. Geomagnetic storms are among the most important phenomenon of space weather effects on Earth. Intense geomagnetic storms can cause severe damage to satellites, communications and power transmission lines (Jordanova et al., 2020 and references therein). The southward interplanetary magnetic field (IMF) B z in solar wind allows magnetic reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…Kumar et al. (2021) has also shown that the electron contribution to the total pressure during a particular CIR driven storm was ∼18% in the dawn sector.…”
Section: Summary and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Kumar et al. (2021) has also shown that the electron contribution to the total pressure during a particular CIR driven storm was ∼18% in the dawn sector.…”
Section: Summary and Discussionmentioning
confidence: 94%
“…Zhao et al (2016) also reported that the electron pressure was higher from midnight to dawn as compared to the noon and dusk sectors. Kumar et al (2021) has also shown that the electron contribution to the total pressure during a particular CIR driven storm was ∼18% in the dawn sector.…”
Section: Summary and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, as parameters that are averaged over longer periods of time tend to show higher statistical correlations without any meaningful increase in association (Simms et al., 2022), this alone could explain the Kp , at a 3 hr cadence, having a higher correlation with flux than that of many other parameters. SymH may be an indirect measure of the free energy available for local wave acceleration of keV electrons up to MeV energies, but is perhaps more representative of inner magnetospheric plasma pressure, about 12% of which is keV electron pressure (Kumar et al., 2021). SymH may be worth testing as a representation of these processes, but the applicability to electron flux in the outer radiation belts appears weak.…”
Section: Drivers Of 40–150 Kev Electrons At Geostationary Orbitmentioning
confidence: 99%
“…In addition, as parameters that are averaged over longer periods of time tend to show higher statistical correlations without any meaningful increase in association (Simms et al, 2022), this alone could explain the Kp, at a 3 h cadence, having a higher correlation with flux than that of many other parameters. SymH may be an indirect measure of the free energy available for local wave acceleration of keV electrons up to MeV energies, but is perhaps more representative of inner magnetospheric plasma pressure, about 12% of which is keV electron pressure (Kumar et al, 2021). SymH may be worth testing as a representation of these processes, but the applicability to electron flux in the outer radiation belts appears weak.…”
Section: Author Manuscriptmentioning
confidence: 99%